The Effect of Using Different Light Colors on the Growth of Nanochloropsis sp - Rehuli damanik (Airlangga University, 2020)
Natural feed Nannochloropsis sp. is one of the limiting factors for cultivated creatures. However, the cultivation of natural food is not yet optimal in terms of quantity, one of the efforts that can be done to optimize this is by using lights produced from sunlight to improve the quality of Nannochloropsis sp. The design in this study was a Completely Randomized Design (CRD) consisting of 4 preparations and 3 replications. The treatments taken are the color of the white light (P1), the color of the red light (P2), Green (P3) and Blue (P4). The parameters that increase are the specific growth rate (LPS), time of doubling, growth curve, water quality. The observations obtained at the time of LPS were collected between 0.200-0.248 cells / ml / day, doubling time 2.806-3.476 then the temperature measurement results were between 30.6-32 0C pH 6.2-7.5, salinity 26-27 ppt and DO 5,7-6,7 ppm. Based on the results of analysis of variance conducted on the given color light has a real influence on the specific growth rate and time multiplication. Keywords: Light, Nannochloropsis sp., Growth